2006
DOI: 10.1002/mus.20578
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of continuous and intermittent vibration effects on rat‐tail artery and nerve

Abstract: Hand-transmitted vibration from powered-tools can cause peripheral vasospasm and neuropathy. A rat-tail model was used to investigate whether the pattern of vibration influenced the type and severity of tissue damage. The tails of awake rats were vibrated continuously or intermittently for a total of 4 hours at 60 HZ, 49 m/s(2). Nerves and arteries were harvested immediately or 24 hours after treatment. Tails subjected to intermittent vibration showed transiently increased sensitivity to thermal stimuli. Inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
38
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 17 publications
6
38
0
Order By: Relevance
“…We have previously reported that nearly half the number of SMC vacuoles induced by 4-hr vibration persist 24 hr later (Govindaraju et al, 2006a). Repeated mechanical displacement in vibrated arteries may shear connections of vacuoles and dislodge them from the parent cell.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…We have previously reported that nearly half the number of SMC vacuoles induced by 4-hr vibration persist 24 hr later (Govindaraju et al, 2006a). Repeated mechanical displacement in vibrated arteries may shear connections of vacuoles and dislodge them from the parent cell.…”
Section: Discussionmentioning
confidence: 98%
“…Structurally similar vacuoles have been observed in SMC of arteries induced to undergo intense vasoconstriction by topical norepinephrine (NE) or epinephrine (Joris and Majno, 1977;Curry et al, 2005b;Govindaraju et al, 2006a). Joris et al, in an elegant series of electron microscopic studies, called the vacuoles herniations because the majority were continuous with the parent cell by slender necks (Joris and Majno, 1977).…”
mentioning
confidence: 84%
“…Rats in the vibration apparatus were observed for signs of discomfort like porphyrin (reddish-black secretions from the eye), excessive vocalization, grinding of teeth and loose stools as described earlier (Govindaraju et al, 2006a).…”
Section: Behavioral Observationmentioning
confidence: 99%
“…However, vibration also consistently induces an increase in oxidative stress and reduction in endothelial-mediated vasodilation 14,16,37) , and these effects were more pronounced in obese than in lean rats. Because obese rats display many of the symptoms seen in humans with metabolic syndrome 11) , we believe that these results suggest that pre-existing vascular dysfunction caused by metabolic syndrome may make workers more susceptible to vibration-induced vascular injury, and put them at greater risk of developing VWF.…”
Section: Fig 6 Dose-dependent Vasodilation To the No Donor Snap Inmentioning
confidence: 99%